NEOLIBERAL CONSTRUCTION OF RELATIONALITY AND OBLIGATION TO A PARENT WITH DEBILITY. (11th November 2018) - Atakere, D; Adams, G
Abstract: Familial interdependence continues to underpin intergenerational relations and familial caring responsibilities and obligations. Interdependence may be especially problematic in modern society due to neoliberal psychological tendencies. Neoliberal psychological tendencies include motivations towards growth, expansion, and taking advantage of opportunities for individual exploration. These tendencies influence how people construct their relationships, as well as their ideas interpersonal obligation. In particular, neoliberalism is compatible with a greater emphasis on personal interests and needs for growth over maintenance of interpersonal networks through obligation. We explored cultural ecological variation in constructions of obligation to a parent with debility in a study of N = 455 participants from Ghanaian and U.S. settings (both European American and African American) characterized by relatively less and more engagement in global modernity. Participants responded to items assessing knowledge, belief, and perception of eldercare; prioritization of financial support; patterns of eldercare provision; and additional social and ecological characteristics. Result support our hypothesized pattern that neoliberal individualistic understanding of relationality leads to a narrowing sense of obligation toward elderly parents. Moreover, evidence for an integrative approach to eldercare was more evident among Ghanaian participants. We discuss implications of results for theories about relationality and for evolving patterns of eldercare provision within close interpersonal networks. Our discussion will show how cross-cultural studies can help to reveal the typically unstated assumptions about family obligation and eldercare that vary across human societies and help alter modern individualism to provide a better quality of life, assurance, and support for elders.